Intergenerational Transmission of Reproductive Behavior in Sweden, 1850-1889 - Paul Rotering (Historical Life Course Studies)
Previous studies have consistently observed intergenerational continuities in childbearing. This study uses individual-level parish records to examine the intergenerational transmission of fertility over the life course of women in Sweden during the fertility transition in the second half of the nineteenth century. Bivariate correlations, event history analysis and Poisson regression models are estimated for a large number of indicators of reproductive behavior. In line with the literature, the findings show evidence of intergenerational fertility correlations. The observed correlations are often small, but show that fertility transmission did occur during the demographic transition. The findings confirm our current understanding of intergenerational transmission and highlight the role of kin members in shaping reproductive outcomes.